Asuhan Akupunktur Pada Kasus Angioma Kavernosa (Aneurisma) Menggunakan Scalp Acupuntur Jiao Shunfa - Toufiq Martin; Mayang Wulandari; Chantika Mahadini; Leny Candra Kurniawan (Journal of Mandalika Literature, 2026)
Cavernous angioma or cavernous malformation is a benign vascular abnormality that frequently occurs in the central nervous system and may cause neurological disturbances such as seizures, headache, motor weakness, and stroke. Conventional medical management of cavernous angioma remains limited, particularly in cases without surgical indications. Acupuncture, as a complementary therapy, may provide clinical benefits in reducing symptoms and improving patients’ quality of life. This study aimed to evaluate the benefits of acupuncture care using scalp acupuncture in a case of cavernous angioma. A qualitative case study approach was applied to one client at an independent acupuncture practice in Jakarta. Data were collected through four diagnostic methods of acupuncture (inspection, auscultation and olfaction, inquiry, palpation), medical diagnostic findings, and clinical evaluations before and after treatment. The results demonstrated that structured scalp acupuncture on motor, sensory, and chorea–tremor areas led to clinical improvement in the client’s main and additional complaints. Scalp acupuncture shows potential as a supportive modality in the management of cavernous angioma